2021
DOI: 10.1103/physrevb.103.l140411
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived electron spin coherence in Ga-doped ZnO at room temperature

Abstract: Electron spin dynamics are studied in Ga-doped ZnO single crystals by time-resolved Faraday and Kerr rotation spectroscopies. Long-lived spin coherence with two dephasing processes is discovered where the characteristic time is up to 5.2 ns at room temperature. Through the dependence measurements of laser wavelength and temperature, the room-temperature long-lived spin signal is attributed to localized electrons. The spin dephasing (relaxation) processes are independent of transverse (longitudinal) magnetic fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The spin dynamics and relaxation mechanism are typically strongly different between the itinerant and localized electrons. It has been demonstrated in conventional III–V and II–VI semiconductors that localized electrons typically have longer spin relaxation times than itinerant electrons, , owing to the fact that the spatial localization of the carrier wave function will suppress the spin relaxation mechanism related to spin–orbit coupling. Also, previous experiments in monolayer TMDs have revealed that itinerant electrons are subject to a strong spin–orbit field that may result in fast spin relaxation and/or the absence of spin precession when applying external transverse magnetic fields B , while localized electrons are unacted-on spin–orbit fields and exhibit precessing spin signals with frequencies proportional only to B . The spin and valley polarization dynamics of itinerant carriers in monolayer TMDs have been extensively investigated by time-resolved spectroscopies such as time-resolved Kerr rotation , and time-resolved photoluminescence. In comparison, many fewer studies have been conducted on the spin and valley properties of localized carriers (wherein most are related to localized excitons and very few are related to localized electrons , ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The spin dynamics and relaxation mechanism are typically strongly different between the itinerant and localized electrons. It has been demonstrated in conventional III–V and II–VI semiconductors that localized electrons typically have longer spin relaxation times than itinerant electrons, , owing to the fact that the spatial localization of the carrier wave function will suppress the spin relaxation mechanism related to spin–orbit coupling. Also, previous experiments in monolayer TMDs have revealed that itinerant electrons are subject to a strong spin–orbit field that may result in fast spin relaxation and/or the absence of spin precession when applying external transverse magnetic fields B , while localized electrons are unacted-on spin–orbit fields and exhibit precessing spin signals with frequencies proportional only to B . The spin and valley polarization dynamics of itinerant carriers in monolayer TMDs have been extensively investigated by time-resolved spectroscopies such as time-resolved Kerr rotation , and time-resolved photoluminescence. In comparison, many fewer studies have been conducted on the spin and valley properties of localized carriers (wherein most are related to localized excitons and very few are related to localized electrons , ).…”
mentioning
confidence: 99%
“…The spin dynamics and relaxation mechanism are typically strongly different between the itinerant and localized electrons. It has been demonstrated in conventional III−V and II−VI semiconductors that localized electrons typically have longer spin relaxation times than itinerant electrons, 4,5 owing to the fact that the spatial localization of the carrier wave function will suppress the spin relaxation mechanism related to spin−orbit coupling. Also, previous experiments in monolayer TMDs have revealed that itinerant electrons are subject to a strong spin−orbit field that may result in fast spin relaxation and/or the absence of spin precession when applying external transverse magnetic fields B, while localized electrons are unacted-on spin−orbit fields and exhibit precessing spin signals with frequencies proportional only to B.…”
mentioning
confidence: 99%